The role of primary care in supporting patients living with and beyond cancer. Issue 3 (September 2018) - Adam, Rosalind; Watson, Eila
Abstract : Purpose of review: The prevalence of cancer survivors is increasing. Those living with and beyond a cancer diagnosis have a range of physical, psychosocial and practical needs. This review aims to discuss the role of primary care in meeting these needs. Recent findings: Patients have increased contact with primary care after a cancer diagnosis but the role of the primary care team in the formal delivery of cancer aftercare is not clearly defined and varies depending on setting and context. Research suggests that both patients and health professionals are receptive to greater involvement of primary care, with informational and personal continuity of care, and good co-ordination of care being particularly valued by patients. Recent evidence indicates that shared care between oncologists and primary care physicians can be as effective as and more cost effective than secondary care-led follow-up, and that primary-care nurses could play a role in optimizing survivorship care. Summary: The four pillars of primary care – contact, comprehensiveness, continuity and coordination – are recurring themes in the cancer survivorship literature and emphasize that the traditional core values of general practice lend themselves to innovative interventions to improve the efficiency and efficacy of survivorship care.